Instagram Endorsement Content Analysis: Depiction of Luxury Lifestyle Representation - Ramadanti, Fajrin; Darsono, Nabila Putri; Yunus, Ulani (International Journal of Science and Society, 2024)
The lifestyle portrayed by an influencer in endorsement content encourages the audience to adopt similar behaviors by using the same products or services. Therefore, influencers with a large follower base can help marketers expand their target audience and potential customer base. Building on previous research, this study aims to examine how Maria Rahajeng's endorsement content on Instagram represents lifestyle. Researchers used the concept of lifestyle and 4R concept (reach, relevance, resonance, and relationship). This research uses a descriptive qualitative approach with content analysis techniques. The results of this study show that there is high engagement in the content uploaded by Maria Rahajeng with topics associated with everyday life which makes the content message acceptable to the audience. In addition, Maria Rahajeng's instagram content also shows interactive elements through the comment column feature. Maria Rahajeng also shows a luxurious lifestyle through the products she advertises and the elegant concept in wrapping her endorsement content. Apart from the luxury products she advertises, Maria Rahajeng also shows a luxurious lifestyle through documentation of her attending exclusive events for influencers.